The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/2231-0762.137627
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization effects of two pediatric dentifrices and one regular dentifrice on artificial carious lesion in primary teeth: An in vitro study

Abstract: Aim:The aim of the following study is to know the efficacy of remineralization of two pediatric dentifrices and one regular dentifrice on artificial carious lesions in primary teeth.Materials and Methods:A total of 21 teeth coated with nail varnish leaving a window of 1 mm were subjected to demineralization for 72 h. These 21 teeth were then sectioned into two equal parts with a diamond disc. The 42 sections obtained were then evaluated under the stereomicroscope and the demineralization values were noted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…from using toothpaste when compared to the immediate salivary pH. It was in agreement with Advani and co-workers (Advani et al 2014) who evaluated the effect of different pediatric fluoride dentifrices on artificial carious lesions in primary teeth and they found that there was increase in salivary PH with using fluoride dentifrices. The decrease in salivary pH after 30 mins.…”
Section: 3stability Of Preparationssupporting
confidence: 87%
“…from using toothpaste when compared to the immediate salivary pH. It was in agreement with Advani and co-workers (Advani et al 2014) who evaluated the effect of different pediatric fluoride dentifrices on artificial carious lesions in primary teeth and they found that there was increase in salivary PH with using fluoride dentifrices. The decrease in salivary pH after 30 mins.…”
Section: 3stability Of Preparationssupporting
confidence: 87%
“…The onset of dental caries requires the establishments of necessary physiochemical conditions for mineral dissolution. [29] Certain chemical agents have the potential to modify this mineral loss caused by organic acids.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Various studies have shown CPP-ACP to decrease demineralization and enhance remineralization of the enamel surface carious lesions as well as remineralization of enamel subsurface lesions in various animal and human in situ trials. 5 …”
Section: Introductionmentioning
confidence: 99%